Freshwater shrimp (Palaemonetes australis) as a potential bioindicator of crustacean health - Webb, Diane (Springer Netherlands, 2011)
Palaemonetes australis is a euryhaline shrimp found in south-western Australian estuaries. To determine if P. australis is a suitable bioindicator species for monitoring the health of estuarine biota, they were exposed to measured concentrations of the polycyclic aromatic hydrocarbon, benzo[a]pyrene (B[a]P) at 0.01, 0.1 or 1 ppm for 14 days under laboratory conditions. At the end of exposure the shrimp were sacrificed for biomarker [ethoxycoumarin O-deethylase (ECOD), 8-oxo-dG concentration, and sorbitol dehydrogenase (SDH) activity] analyses. Gender did not appear to influence biomarker responses of the shrimp in this study. ECOD activity was induced in the treatment groups in a linear fashion from 3 (0.01 ppm) times to 12 (1 ppm) times the negative controls. 8-oxo-dG concentration was reduced 3 times in treatment groups below the controls suggesting impaired DNA repair pathways. There was no increase in SDH, signifying hepatopancreatic cell damage had not occurred in any treatment group. The response of P australis to B[a]P exposure indicates that this crustacean is suitable bioindicator species for both laboratory studies and field monitoring. A combination of ECOD and SDH activities and 8-oxo-dG concentration represent a suitable suite of biomarkers for environmental monitoring of the sublethal effects of organic pollution to crustaceans from an estuarine environment.